Associations of PNPLA3 rs738409 Polymorphism with Plasma Lipid Levels: A Systematic Review and Meta-Analysis - Luo, Zhi; Liu, Yang; Li, Hang; Zhou, Yawen; Peng, Yuanyuan; Lin, Xuan; Fang, Ying; Wan, Jing; Wei, Baozhu (Hormone and Metabolic Research, 2022)
Accumulating evidence has shown that the rs738409 polymorphism of patatin-like phospholipase domain-containing 3 (PNPLA3) is associated with non-alcoholic fatty liver disease (NAFLD). Since NAFLD has been reported to be associated with lipid metabolism, this study is conducted to explore whether the rs738409 polymorphism of PNPLA3 was associated with lipid levels. By searching PubMed and the Cochrane database from May 31, 2020, to June 30, 2021. Sixty-three studies (81 003 subjects) were included for the analysis. The consistent findings for the associations of rs738409 polymorphism with lipid levels were the significantly decreased triglycerides (TG) (SMD=−0.04, 95% CI=−0.07 to −0.01, p=0.02) and total cholesterol (TC) (SMD=−0.03, 95% CI=−0.05 to −0.01, p<0.01) levels. Subgroup analysis indicated that the associations of rs738409 polymorphism with TG and TC levels were stronger in Caucasians, obesity patients, and adult subjects than in Asians, T2DM patients, and children subjects. The rs738409 polymorphism of PNPLA3 was associated with lower TG and TC levels in Caucasians, obese and adult subjects, which may contribute to the reduced coronary artery disease (CAD) risk between PNPLA3 rs738409 polymorphism and CAD.
Keywords: PNPLA3; rs738409; polymorphism; lipids and cholesterol; CAD